Effective cellulose nanocrystal imaging using transmission electron microscopy. (15th April 2018) - Stinson-Bagby, Kelly L.; Roberts, Rose; Foster, E. Johan
Highlights: An improved protocol for preparing TEM samples of CNCs is proposed. No radioactive stain or altering TEM grid surface properties involved. A dunking rinse method controls over-application of stain. Troubleshooting table to resolve common issues when imaging CNCs. Abstract: Characterization of cellulose nanocrystals (CNCs) is often complex and tedious. With their increased use for biological materials, polymer reinforcing agents, and other applications, better characterization methods of CNCs are needed to ensure product quality. However, because of their small size, hydrogen bonding, and low electron density, individual CNCs are difficult to image with high resolution and magnification using electron microscopy. Methods to help counter these challenges include staining for increased contrast and techniques to increase dispersion. This work tested several stains, dispersing agents, and sample supports to find a consistent method of individualizing CNCs and providing good contrast for imaging in transmission electron microscopy (TEM). The most consistent method found uses a low concentration of CNCs, bovine serum albumin as a dispersing agent, and Nanovan ® as the contrasting stain on a silicon monoxide-coated Formvar TEM grid.